Comparative Analysis of the Chalcone-Flavanone Isomerase Genes in Six Citrus Species and Their Expression Analysis in Sweet Orange (Citrus sinensis) - Wan, Quan; Bai, Tingting; Liu, Minmin; Liu, Ying; Xie, Yating; Zhang, Tao; Huang, Min; Zhang, Jinlian (Frontiers in Genetics, 2022)
Citrus fruit contains rich nutrients which is edible and of officinal value. Citrus flavanones are widely used in the treatment of cardiovascular and other diseases, and they are a foundational material of Chinese medicine. The chalcone-flavanone isomerase (CHI) plays a key role in flavanone synthesis. Therefore, we comprehensively analyzed CHI genes in Citrus species. Here, thirty CHI genes were identified for the first time in six Citrus species, which were divided into CHI and FAP groups. Evolutionary analysis showed that CHI gene members were highly conserved and were an ancient family. All CsCHI genes showed the highest expression level after the second physiological fruit-falling period in C. sinensis. CsCHI1 and CsCHI3 were highly expressed at 50 days after the flowering (DAF) stage in albedo. The expression of CsFAP2 and CsCHI3 genes at the 50 DAF stage was 16.5 and 24.3 times higher than that at the 220 DAF stage, respectively. The expression of CsCHI1, CsCHI3, and CsFAP2 genes in the peel was higher than that in the pulp, especially in common sweet orange. The CsCHI3 gene maintained a high expression level in the epicarp and juice sac at all periods. The members of CHIs interacted with chalcone synthase (CHS), flavonol synthase/flavanone 3-hydroxylase (FLS) and naringenin, and 2-oxoglutarate 3-dioxygenase (F3H) to form heterodimers, which might together play a regulatory role and participate in the flavonoid pathway. This study will provide the basis for the selection of flavonoids in plant tissues and periods and fundamental information for further functional studies.